1995
DOI: 10.1177/1077727x9502300405
|View full text |Cite
|
Sign up to set email alerts
|

West African Apparel Textiles Depicted in Selected Magazines from 1960 to 1979: Application of Cultural Authentication

Abstract: The purpose of the study was to determine the extent of West African influence on apparel textiles in the United States during the 1960s and 1970s and whether the concept of cultural authentication could be applied to the borrowing of West African textiles for use in the United States. A small number of West African and West‐African‐influenced apparel textiles were found. More illustrations of these textiles were found in Ebony in the 1960s than in other magazines, whereas Mademoiselle had slightly more illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Ingvoldstad, DeLong, and Koh's study of jeans (1994) resulted in the authors' suggestion that the order of the process described by Eicher and Erekosima (1980) may not be necessary for CA to take place. The results of Mead and Pedersen's (1995) research on West African textiles revealed no evidence of either the characterization or incorporation stages, leading the authors to question both the ordering and the necessity of all the stages. The authors noted that ''it is equally possible that in other cultures [cultural authentication] occurs somewhat differently'' (p. 447).…”
Section: Theoretical Framementioning
confidence: 96%
“…Ingvoldstad, DeLong, and Koh's study of jeans (1994) resulted in the authors' suggestion that the order of the process described by Eicher and Erekosima (1980) may not be necessary for CA to take place. The results of Mead and Pedersen's (1995) research on West African textiles revealed no evidence of either the characterization or incorporation stages, leading the authors to question both the ordering and the necessity of all the stages. The authors noted that ''it is equally possible that in other cultures [cultural authentication] occurs somewhat differently'' (p. 447).…”
Section: Theoretical Framementioning
confidence: 96%